Risk Analysis of Greenhouse-Based Paprika Farming Using Failure Mode and Effect Analysis (FMEA) - Ella Stevani Simbolon; Teguh Soedarto; Sri Widayanti (The University of Lampung, 2026)
Bell pepper is a high-value horticultural commodity with strong development potential in Indonesia, including in Tutur District, Pasuruan Regency, East Java. However, productivity in greenhouse-based cultivation often fluctuates due to various production risks. This study aimed to identify and prioritize major risks in greenhouse bell pepper farming using the Failure Mode and Effect Analysis (FMEA) method. The research location was purposively selected, involving 66 farmers. Primary and secondary data were collected and analyzed using descriptive analysis and FMEA. The results identified 17 risk factors affecting bell pepper production. Major risks included high rainfall during the rainy season, water shortages during the dry season, strong winds, pest and disease attacks, declining selling prices, increasing input costs, and limited technical knowledge. Based on Risk Priority Number (RPN) analysis, the most critical risks were thrips pest attacks (RPN 109.12), high rainfall (RPN 52.52), and strong winds (RPN 38.31). These risks require priority mitigation to improve productivity and sustainability of greenhouse bell pepper farming.